Apolipoprotein B and Lipid Profile among Patients Diagnosed with Acute Myocardial Infarction. - Shrestha, Deependra; Yadav, Binod Kumar; Gajurel, Ratna Mani; Sharma, Vijay Kumar; Raut, Mithlesh; Bhattarai, Aseem; Shrestha, Sweta; Ghimire, Sapana; Shakya, Basu; Tuladhar, Eans Tara (Nepalese Heart Journal, 2022)
Background and Aims: Acute myocardial infarction (AMI) is a leading cause of death among men and women globally and often a sequelae to atherosclerotic cardiovascular disease [ASCVD]. Atherosclerosis is linked with abundance of Apolipoprotein B [ApoB] and the lipid constituents they are carrying. There are limited data of ApoB status and its usage alongside conventional lipid profile parameters among AMI patients of Nepal. The study aim estimate the blood level of ApoB and determine its usefulness alongside analysis of total cholesterol[TC], triglycerides[TG], high density lipoprotein cholesterol[HDL-C], low density lipoprotein cholesterol[LDL-C],non-HDL cholesterol, LDL/HDL ratio in AMI patients . Methods: This was a hospital based comparative cross-sectional study conducted in patients attending Manmohan Cardiothoracic Vascular and Transplant Centre [MCVTC] and Shahid Gangalal National Heart Centre[SGNHC] over a period of 1 year. Seventy three diagnosed AMI patients were enrolled using convenient sampling technique. Forty patients undergoing regular general health checkup in Tribhuvan University Teaching Hospital [TUTH ] were recruited as controls. Laboratory analysis was carried by turbidimetric method for Apolipoprotein B and enzymatic methods for lipid profile parameters in department of Biochemistry, TUTH. Data was analyzed using SPSS version 18.0. Results: AMI was seen in the mean age of 56±11 years with male predominance. Mean level and standard deviation of ApoB was 99.2±17.7mg/dl in AMI which was significantly higher than controls. ApoB showed moderate correlation with non-HDL cholesterol [r=0.378,p<0.001] and HDL-C[r= -0.490,p< 0.001]. Conclusion: Our study found a significantly higher level of ApoB in AMI with moderate correlation with non HDL-C and HDL-C, necessitating its usage as a complementary marker to conventional lipid profile.